The hypothalamic–pituitary–thyroid axis, depression and risk of suicide: commentary, Luo et al - Charles B. Nemeroff (BJPsych Open)
There is a considerable literature on the relationship of thyroid function with risk of depression and responsiveness to depression treatment. This literature is briefly reviewed here, followed by a focus on the incremental advance provided by the findings of Luo et al on autoimmune thyroiditis and suicide attempts.